Interrelationships among workload, illness severity, and function on return to work following acute respiratory distress syndrome. Issue 2 (March 2023) - Su, Han; Thompson, Hilaire J.; Pike, Kenneth; Kamdar, Biren B.; Bridges, Elizabeth; Hosey, Megan M.; Hough, Catherine L.; Needham, Dale M.; Hopkins, Ramona O.
Abstract: Background: Inability to return to work (RTW) is common after acute respiratory distress syndrome (ARDS). Objectives: The aim of this study is to examine interrelationships among pre-ARDS workload, illness severity, and post-ARDS cognitive, psychological, interpersonal, and physical function with RTW at 6 and 12 months after ARDS. Methods: We conducted a secondary analysis using the US multicentre ARDS Network Long-Term Outcomes Study. The US Occupational Information Network was used to determine pre-ARDS workload. The Mini-Mental State Examination and SF-36 were used to measure four domains of post-ARDS function. Analyses used structural equation modeling and mediation analyses. Results: Among 329 previously employed ARDS survivors, 6- and 12-month RTW rates were 52% and 56%, respectively. Illness severity (standardised coefficients range: −0.51 to −0.54, p < 0.001) had a negative effect on RTW at 6 months, whereas function at 6 months (psychological [0.42, p < 0.001], interpersonal [0.40, p < 0.001], and physical [0.43, p < 0.001]) had a positive effect. Working at 6 months (0.79 to 0.72, P < 0.001) had a positive effect on RTW at 12 months, whereas illness severity (−0.32 to −0.33, p = 0.001) and post-ARDS function (psychological [6 months: 0.44, p < 0.001; 12 months: 0.33, p = 0.002], interpersonal [0.44, p < 0.001; 0.22, p = 0.03], and physical abilities [0.47, p < 0.001; 0.33, p = 0.007]) only had an indirect effect on RTW at 12 months mediated through work at 6 months. Conclusions: RTW at 12 months was associated with patients' illness severity; post-ARDS cognitive, psychological, interpersonal, and physical function; and working at 6 months. Among these factors, working at 6 months and function may be modifiable mediators of 12-month post-ARDS RTW. Improving ARDS survivors' RTW may include optimisation of workload after RTW, along with interventions across the healthcare spectrum to improve patients' physical, psychological, and interpersonal function.